Effect of Educational Program on Nurses Essential Care Practices of Newborn Baby - Razia Kousar, Muhammad Afzal, Kousar Parveen, Sadia Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nurses essential care practices are important for the survival, growth, and development of a newborn baby. The care of newborn depends on the essential care practices of the nurses. In spite of its essentiality, most nurses in clinical settings have incompetent essential care practices regarding newborn baby. The essential care practices of newborn baby could be improved by implementing educational program. So, there is a dire need of educational intervention on essential care practices of newborn baby. Objective: To see the effect of educational program on nurses essential care practices of newborn baby. To find out association between sociodemographic characteristics and nurses essential care practices of newborn baby. Study Design: Quasi experimental study Materials and Methods: A Quasi experimental study included 48 registered nurses were selected by using simple random sampling technique. A twelve weeks educational intervention consists of PowerPoint lectures on nurses essential care practices, audio visual demonstration and hands on workshop practice sessions were given by the expert of this field to registered nurses on caring of newborn baby. Data on nurse’s practices were collected two times before and after the intervention via validated tools. Results: The study showed a significant (p<0.001) change in nurses essential care practices after educational intervention. Nearly, all nurses had incompetent practices before educational intervention. The practices had been competent as 45(93.8%) from 8(16.7%).There was statistically significant relationship between age and post practices while insignificant relationship was shown among total years of experience, experience in department and department name as well in post-test. Conclusion: The educational interventions significantly improve nurses essential care practices of newborn baby in both Tertiary care Hospitals of Bahawalpur.